The Effect of Aluminum Addition Ratio as Filling Material of PLA Toward PLA Filament Electrical Conductivity on 3D Printing Applications - Ridwan, Firman; Zuliantoni, Zuliantoni (METAL: Jurnal Sistem Mekanik dan Termal, 2024)
Â The electronic waste of daily electronic goods evokes environmental pollution because electronic waste is difficult to decompose in nature and it is also toxic to the environment and humans. The way to minimize environmental pollution from electronic waste is by making polymer composites for conductive material purposes. Polylactic acid (PLA) has the potential as a polymer matrix. PLA has a non-toxic advantage and it is easily decomposed in nature because PLA is made from organic material.The extruder machine is used to make PLA filament with aluminum filling. When made the filaments, the ratio of each mixture was varied to obtain a filament with a mixture ratio that produced the best conductivity. The four-point probe test tool is used to measure the resistivity of each specimen to find out which specimen with the mixture ratio has the best conductivity value.The electrical conductivity obtained from the ratio of 10% Al is 6.78 S/m; 20% Al is 10 S/m; 30% Al is 31.44 S/m; 40% Al is 24.15 S/m. The best electrical conductivity results was obtained in the 70% PLA and 30% Al mixture ratio with an electrical conductivity value is 31.44 S/m while the lowest electrical conductivity was obtained in the 90% PLA and 10% Al mixture ratio with an electrical conductivity value is 6.67 S/m